ETHNOBOTANICAL STUDIES IN SOUTH WEST BURKINA FASO: TRADITIONAL USES OF PLANT SPECIES FROM GALLERY FORESTS IN SENOUFO ETHNIC AREA, ESPECIALLY BY TRADITIONAL HEALERS AND DOZOS HUNTERS - Marc, O.; Paulin, O.; Sita, G. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
In the South West part of Burkina Faso, both provinces of Comoé and Léraba are characterized by an accented relief, a humid climate and many places hard to reach. Many permanent rivers show developed gallery forests, which have not been well-studied both from botanical and ethnobotanical points of view. We present results concerning ethnobotanical studies carried out between April 2006 and December 2007 on traditional uses of plants from gallery forests, especially those plants used by people belonging to Senoufo ethnic community, which are in a large majority in study area. We mainly worked with traditional healers and Dozos hunters, a local secret confraternity, but also with old people, especially women. Our survey led us to collect data on about 61 plant species, representing 51 genera and 34 families. Plants used for nutrition, medicine (malaria, hypertension, diabetes, sickle – cell anaemia, etc.), cosmetics, native craft industry, hunting, and animist rituals were registered with vernacular names and methods of use. Many species typical of the Guinean phytogeographical area were found (Uapaca togoensis Pax., Voacanga africana Stapf.), even though Burkina Faso flora belongs mainly to Soudanian and Sahelian areas. We observed that due to agricultural practices, gallery forests are threatened in the studied area. Discussing with women, we could identify two species with an economic potential, Carapa procera DC. and Pentadesma butyracea Sab, (traditional production of vegetal oil and butter used in food and cosmetics). We conclude that helping women to sell their products could encourage populations to protect gallery forest biodiversity.